TLR4 deletion increases basal energy expenditure and attenuates heart apoptosis and ER stress but mitigates the training-induced cardiac function and performance improvement - de Vicente, Larissa G.; Muñoz, Vitor R.; Pinto, Ana P.; Rovina, Rafael L.; da Rocha, Alisson L.; Marafon, Bruno B.; Tavares, Maria Eduarda de A. [UNESP]; Teixeira, Giovana R. [UNESP]; Ferrari, Gustavo D.; Alberici, Luciane C.; Frantz, Fabiani G.; Simabuco, Fernando M.; et al. (Elsevier, 2021)
Strategies capable of attenuating TLR4 can attenuate metabolic processes such as inflammation, endoplasmic reticulum (ER) stress, and apoptosis in the body. Physical exercise has been a cornerstone in suppressing inflammation and dysmetabolic outcomes caused by TRL4 activation. Thus, the present study aimed to evaluate the effects of a chronic physical exercise protocol on the TLR4 expression and its repercussion in the inflammation, ER stress, and apoptosis pathways in mice hearts. Echocardiogram, RT-qPCR, immunoblotting, and histological techniques were used to evaluate the left ventricle of wild-type (WT) and Tlr4 knockout (TLR4 KO) mice submitted to a 4-week physical exercise protocol. Moreover, we performed a bioinformatics analysis to expand the relationship of Tlr4 mRNA in the heart with inflammation, ER stress, and apoptosis-related genes of several isogenic strains of BXD mice. The TLR4 KO mice had higher energy expenditure and heart rate in the control state but lower activation of apoptosis and ER stress pathways. The bioinformatics analysis reinforced these data. In the exercised state, the WT mice improved performance and cardiac function. However, these responses were blunted in the KO group. In conclusion, TLR4 has an essential role in the inhibition of apoptosis and ER stress pathways, as well as in the training-induced beneficial adaptations.
Keywords: Bioinformatics; Knockout model; Molecular signaling pathways; Morphofunctional characteristics; Regular exercise